THE ROLE OF TEACHING ASSISTANTS IN SUPPORTING STUDENTS WITH SPECIAL EDUCATIONAL NEEDS IN HONG KONG (Proceedings of International Conference on Special Education, 2015)
Teaching assistants (TAs) have undergone an exceptional development internationally in the past decade. TAs have been employed in supporting students with special educational needs (SEN) in many countries. The continual development of TAs has transformed its role from the traditional classroom helper to one that encompasses a range of tasks with a focus on engaging students with SEN in educational learning and key aspects of social, emotional and behavioural developments with more inclusive approaches. This paper studied the role of TAs in supporting students with SEN in government aided primary and secondary schools in Hong Kong. A mixed methodology was employed, combining a quantitative survey and qualitative semi-structured interviews in order to collect “mixed” forms of data. 500 questionnaires were distributed and 113 valid responses obtained. Six schools (three primary, three secondary) participated in the qualitative part of the study. Data gathered identifies clearly a lack of clarity and understanding on how the role of TAs may be most effectively utilized in Hong Kong. A clarification of the role is essential if the effective deployment of TAs is to be achieved to support the inclusion agenda. Key findings that relates to the role of TAs who have a direct bearing on learning, social and emotional developments for students with SEN in mainstream schools will be discussed in this paper. As the number of TAs working in supporting inclusion continuous to grow, it is important for the school leaders, policy makers and academic researchers to draw from this baseline data and studies from other countries so as to find further ways of improving the quality of support by TAs to support inclusion and ensure that this brings the utmost possible effects.